The Effect of Parental Attention, Social Media and Religiosity on the Morals of Students - Endang Ekowati; Nyayu Khodijah; Abdurrahmansyah Abdurrahmansyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aimed to determine the effect of parental attention, social media, and religiosity on adolescent morals at a Madrasah Aliyah Negeri, South Lampung. The research was quantitative. The population in the study was 450 students, with a proportional random sampling technique; the sample used was 82 students. The data collection method used was a questionnaire. The method of data analysis was done by descriptive analysis and path analysis. The study showed that first, the effect of parental attention on adolescent morals was 13% in the low category. Second, the influence of social media on adolescent morals was 32% in the medium category. Third, the influence of religiosity on adolescent morals was 53% in a strong category. And fourth, the correlation of the effect of parental attention, social media, and religiosity on adolescent morals simultaneously was 57%. Thus, parental engagement, social media, and religiosity positively affected adolescent morals.